Survey for legume and cereal viruses in Libya - Abukraa, H.; Kumari, Safaa; Bshia, F. (Arab Society for Plant Protection, 2022)
A field survey was conducted during March and April 2010, to identify viral diseases affecting cereal and legume crops in different regions of Libya. A total of 3706 barley and wheat samples were collected randomly in addition to 187 symptomatic samples from 22 barley and 20 wheat fields. Moreover, 34 symptomatic legume samples were collected from two faba bean fields and one field each of of lentil, chickpea, Vicia sativa, Vicia ervillia and Vicia narbonesis. All samples were tested at ICARDA Virology Laboratory by tissue blot immunoassay (TBIA) using specific antibodies. Results of random cereal samples showed that Barley yellow dwarf virus-PAV (BYDV-PAV) was more common (12.6%) in wheat and barley samples, followed by Wheat dwarf virus (WDV) (1.1%). In symptomatic samples, BYDV-PAV was also the most common (45 out of 187 samples tested were infected: 45/187), followed by WDV (23/187), Barley yellow striate mosaic virus (BYSMV) (40/187) and Maize streak virus (MSV) (7/187). In legume fields, Soybean dwarf virus (SbDV) 13 out of 34 samples tested were infected (13/34) was the most common, followed by Bean leafroll virus (BLRV) (12/34), Chickpea chlorotic stunt virus (CpCSV) (5/34) and Beet western yellows virus (BWYV) (4/34). Serological results were confirmed by amplification with polymerase chain reaction (PCR) using specific primers. This is the first report of WDV, MSV and BYSMV on cereal crops, and BLRV, BWYV, SbDV and CpCSV on legume crops in Libya.